Keterampilan Komunikasi – Pengetahuan dan Perilaku Berbahasa–Penentu Keberhasilan Industri Pariwisata di Malaysia - Ahmad, Anzaruddin (Jurnal ILMU KOMUNIKASI, 2008)
Abstract: It is clear that the aggresive promotions activities for tourism sector is vety important. It contributes to increase the Malaysian’ economic condition. Predicted the number of overseas tourism visitors to Malaysia increase to 21.5 milion people in 2008, up to 5% from those in 2007. It is followed by the raising of revenue in this sector, from RM 44.5 bilion in 2007 up to RM 49 milion in 2008. In 2010 Malaysia hopes there will be 24.6 milion people visit to Malaysia. It will be followed by the raising of revenue in tourism sector and also of working opportunities. To attantion the goals, it needs many professional human resources. Promotion activities and creating of tourism products, without serious effeorts and thingking for developing the professional tourism; human resources, will be not effective. This paper intended to discuss the effort to improve the quality of human resources in tourism industry, especially in the area of the communication competence.